Efektivitas Penggunaan Aplikasi Bima terhadap Pengelolaan Stok Opname B21 Digital Printing - Elvanda Sahra Shabrina; Fani Khoirotunnisa (Universitas Muhammadiyah Surabaya, 2025)
The purpose of this study was to determine the effectiveness of using the bima application on stock management of opname b21 digital printing. Digital-based systems have changed the way of working in the printing world by speeding up processes and increasing efficiency. This research uses a qualitative approach that aims to understand the phenomena experienced by research subjects, such as behavior, perceptions, motivations, and actions. This application is effectively integrated in the company's operational activities. The